Academic dishonesty: a cause for concern? / Aishah Musa and Junaida Ismail - Musa, Aishah; Ismail, Junaida (Universiti Teknologi MARA, 2021)
Academic dishonesty is a global issue that should be improved and taken into consideration seriously by many parties. A previous study done by Maramark & Maline, 1993 (p.2) showed that the researchers stressed on academic dishonesty and its needs to be garnered as a national attention and serious problem among college students. There are several actions that are related to academic dishonesty such us cheating on tests, cheating in assignments, or plagiarizing papers. This paper reveals the results that are related to the academic dishonesty perceptions among the students who enrol in a public university in Malaysia. A set of questionnaires was distributed via class WhatsApp to the respective respondents. In total 536 students from 5 faculties responded to the questionnaire. The results show that 75% of the students admitted that they were aware of the existence of Buku Peraturan Akademik and 59.1% declared that they had read the Buku Peraturan Akademik. Buku Peraturan Akademik refers to the main rules and regulations provided by the public university to all the students who enrol in the University. The purpose of this Buku Peraturan Akademik is to inform the students what are ‘the dos and the don’ts’ that they have to follow during their studies. It is hoped that this paper is able to give some insights for the students, researchers and many other parties for the need to improve on the issue of academic dishonesty.